2006
DOI: 10.1103/physrevlett.96.245503
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separating Bulk Metallic Glass: A Hierarchical Composite

Abstract: Phase separating systems present a unique opportunity for designing composites with hierarchical microstructure at different length scales. We report here our success in synthesizing phase separating metallic glasses exhibiting the entire spectrum of microstructural possibilities expected from a phase separating system. In particular, we report novel core shell and hierarchical structures of spherical glassy droplets, resulting from critical wetting behavior and limited diffusion. We also report synthesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 28 publications
1
71
1
Order By: Relevance
“…A pertinent question is how to understand these systemspecific behaviours in a general physical scenario. To appreciate this question, we consider the concept of enthalpy of mixing for MGs as it provides an effective way to the understanding of many chemical-related issues in MGs, such as glass-forming ability 33,34 , mechanical properties 37 , phase separation [38][39][40] , as well as crystallization and devitrification of MGs 41 . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A pertinent question is how to understand these systemspecific behaviours in a general physical scenario. To appreciate this question, we consider the concept of enthalpy of mixing for MGs as it provides an effective way to the understanding of many chemical-related issues in MGs, such as glass-forming ability 33,34 , mechanical properties 37 , phase separation [38][39][40] , as well as crystallization and devitrification of MGs 41 . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, phase separated metallic glasses were successfully prepared in several alloy systems: Zr-Y-Co-Al [7], Ni-Nb-Y [8], ZrNd-Al-Co [9], Cu-(Zr,Hf)-(Gd,Y)-Al [10], and Zr-(Ce,Pr,Nd)-Al-Ni [11]. In all these cases, phase separation leads to a special microstructure with a length-scale up to several micron and some self similar features are observed by transmission electron microscopy (TEM) [6,12,13].…”
Section: Introductionmentioning
confidence: 95%
“…Basically, two types of structures are observed in liquid-liquid phase separation owing to different separation mechanisms: interconnected-type structure due to spinodal decomposition, and droplet-type structure due to the nucleation and growth mechanism 6 . Park et al 10 clearly showed that the interconnected-type or droplet-type structure depends on the alloys composition in the miscibility gap. According to the glass-forming ability of the separated liquid phases, an amorphous/amorphous or amorphous/crystalline structure can be obtained as composite structures 6,10,11 .…”
Section: Introductionmentioning
confidence: 99%